COVID‐19 elicits an impaired antibody response against SARS‐CoV‐2 in patients with haematological malignancies. (16th July 2021) - Passamonti, Francesco; Romano, Alessandra; Salvini, Marco; Merli, Francesco; Porta, Matteo G. Della; Bruna, Riccardo; Coviello, Elisa; Romano, Ilaria; Cairoli, Roberto; Lemoli, Roberto; Farina, Francesca; Venditti, Adriano; et al.
Summary: COVID‐19 is associated with high mortality in patients with haematological malignancies (HM) and rate of seroconversion is unknown. The ITA‐HEMA‐COV project (NCT04352556) investigated patterns of seroconversion for SARS‐CoV‐2 IgG in patients with HMs. A total of 237 patients, SARS‐CoV‐2 PCR‐positive with at least one SARS‐CoV‐2 IgG test performed during their care, entered the analysis. Among these, 62 (26·2%) had myeloid, 121 (51·1%) lymphoid and 54 (22·8%) plasma cell neoplasms. Overall, 69% of patients (164 of 237) had detectable IgG SARS‐CoV‐2 serum antibodies. Serologically negative patients (31%, 73 of 237) were evenly distributed across patients with myeloid, lymphoid and plasma cell neoplasms. In the multivariable logistic regression, chemoimmunotherapy [odds ratio (OR), 3·42; 95% confidence interval (CI), 1·04–11·21; P = 0·04] was associated with a lower rate of seroconversion. This effect did not decline after 180 days from treatment withdrawal (OR, 0·35; 95% CI: 0·11–1·13; P = 0·08). This study demonstrates a low rate of seroconversion in HM patients and indicates that treatment‐mediated immune dysfunction is the main driver. As a consequence, we expect a low rate of seroconversion after vaccination and thus we suggest testing the efficacy of seroconversion in HM patients.